Hasil Pengamatan Diagnosa Klinik Terhadap Diagnosa Patologi pada Penderita Radang Usus Buntu - Prawito, Prawito (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
The purpose of this paper is to review 309 patients of appendicitis operated in the Department of Surgery, Gadjah Mada University Hospital, Yogyakarta, between 1972 - 1976. Among the pa. tients 81 are males and 228 are females. The peak incidence of appendicitis is between 15 - 20 years of age. Results of the clinical diagnosis compared with the pathological diagnosis are as follows;81,8% is chronic appendicitis; 44,4% is acute appendicitis; 64,4% is chronic appendicitis with acute exacerbation; 60% is periappendicular infiltrate and 1,9% is normal appendix.Fecaliths within the lumen-of the appendix are found in 136 patients (44%); eggs of elscaris in 8 patiens (2,6%).Key Words: appendicitis - periappendicular infiltrate - Ascaris - normal appendix - fccaliih